Convenient Synthesis of 68Ga‐Labeled Gadolinium(III) Complexes: Towards Bimodal Responsive Probes for Functional Imaging with PET/MRI1. Issue 38 (28th August 2013) - Notni, Johannes; Hermann, Petr; Dregely, Isabel; Wester, Hans‐Jürgen
<x xml:space="preserve">Abstract</x> A killer application? Recently, fully integrated full‐body positron‐emission tomography (PET) and magnetic‐resonance imaging (MRI) scanners were brought to market, allowing simultaneous recording of complementary 3D data sets. By using bimodal PET/MRI probes (see figure), in vivo 3D mapping of various parameters with medical relevance could become feasible.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>